2012
DOI: 10.1002/cmmi.1499
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of SPIO‐labeled human pancreatic cancer cell line BxPC‐3

Abstract: The survivin gene is highly expressed in pancreatic cancer. The purpose of this study was to design and synthesize functionalized magnetic iron oxide nanoparticles (MNPs) targeting survivin gene for the detection of pancreatic cancer. The pancreatic cancer cell line BxPC-3 with survivin gene expression was selected in this study. The healthy lung fibroblast cell was used as a control. Chitosan-coated MNPs (CS@MNPs) and antisense oligodeoxynucleotide of survivin gene were conjugated to MNPs to give Sur-MNPs. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Magnetic nanoparticles (MNPs) can induce changes in T2-or T2*-weight MR images and have been considered as good carriers for targeted molecules with high biocompatibility and low toxicity ( Vuong et al, 2012 ). Optical imaging and/or MR imaging has been applied for pancreatic cancer imaging in previous studies ( Yang et al, 2009 ; Tong et al, 2013 ; Wang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic nanoparticles (MNPs) can induce changes in T2-or T2*-weight MR images and have been considered as good carriers for targeted molecules with high biocompatibility and low toxicity ( Vuong et al, 2012 ). Optical imaging and/or MR imaging has been applied for pancreatic cancer imaging in previous studies ( Yang et al, 2009 ; Tong et al, 2013 ; Wang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted molecules should be highly expressed in cancer cells but absent or under-expressed in normal adjacent tissues ( Yang et al, 2009 ). To find such target molecules, CA19.9 ( Houghton et al, 2015 ), urokinase plasminogen activator ( Yang et al, 2009 ), claudin-4 ( Neesse et al, 2013 ), surviving( Tong et al, 2013 ; Wang et al, 2016 ), insulin-like growth factor-1 receptor (IGF-1R) ( Park et al, 2016 ; England et al, 2016 ), integrin αvβ6 ( Liu et al, 2014 ), integrin αvβ3 ( Trajkovic-Arsic et al, 2014 ) and galectin-1 ( Rosenberger et al, 2015 ) have been tested in pancreatic cancer imaging. Kelly et al (2008) first identified that plectin-1 is highly expressed in invasive pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the value of SPIO for targeted imaging lies in the fact that the SPIO surface can be packaged and subsequently combined with appropriate targeting ligands. In recent years, some scholars [ 19 23 ] have studied the design scheme and biological characteristics of the molecular imaging application of SPIO and believe that to ensure that SPIO has hydrophobic and certain toxic properties and is uniformly distributed in the ferrofluid the selection of the surface package material is critical. The material used for the surface coating of the magnetic particles not only must be nontoxic and biocompatible but also must allow the targetable delivery with particle localization within a specific area.…”
Section: Contrast Agents For Mr Molecular Imagingmentioning
confidence: 99%
“…More recently, the survivin gene, which is a potential marker of PC, has been regarded as a targeting gene, and chitosan-coated magnetic iron oxide particles (MNPs) have been regarded as imaging probes for the detection of PC [ 19 ]. Chitosan-coated MNPs (cs@MNPs) and antisense oligodeoxynucleotides of the survivin gene were conjugated to MNPs to produce Sur-MNPs.…”
Section: Mr Target Molecular Imaging For Pcmentioning
confidence: 99%
“…Survivin gene, which is a member of the inhibitor of apoptosis family, is abundantly expressed in the serum of most pancreatic cancer patients. 16, 17 Tong et al 18 synthesized a survivin gene-targeted magnetic iron oxide nanoparticle with high stability and without any toxicity. The magnetic molecular probe selectively targeted the pancreatic cancer cells with survivin gene expression.…”
mentioning
confidence: 99%